Analysis of Difficulty of Student’s Geometry Problem Solving Based on Van Hiele’s Thinking Theory with Macromedia Flash - Siagian, Philips Pasca G; Sinaga, Bornok; Mulyono, Mulyono (Universitas Ahmad Dahlan, 2019)
This study aims to describe the level of students' geometry thinking based on Van Hiele's thinking theory, the level of students' geometric problem solving abilities, and analyzing students' difficulties in solving geometric problems. This type of research is qualitative descriptive research. The researcher took six research subjects consisting of low, medium, and high level geometry problem solving abilities to be interviewed and analyzed the types of difficulties experienced. The results of this study indicate that there are 26 students reaching level 0 (visualization), 21 students reach level 1 (analysis), 13 students reach level 2 (informal deduction), 6 students reach level 3 (deduction) and no one can reach level 4 (rigor). Furthermore, there are 13 students who have a low level of problem solving ability, 7 students have a medium level of problem solving ability, and 6 students have a high level of problem solving ability. The difficulties experienced by the research subject are described in each problem.